Rural pensions, intra-household bargaining, and elderly medical expenditure in the People's Republic of China - Zeyuan Chen; Albert Park (Asian Development Bank (ADB), 2023)
The rural elderly in the People's Republic of China spend less on medical expenditures as they age despite declining health, which raises welfare concerns. This paper investigates the role of intra-household bargaining power on health expenditures of the elderly by evaluating the impact of cash transfers from a new social pension program. The program provided windfall payments to those above age 60, making it possible to employ a regression discontinuity design based on age of eligibility to estimate causal effects. Using data from the 2011 and 2013 waves of the China Health and Retirement Longitudinal Study, we find that receiving pension payments increases both the utilization of outpatient care and outpatient expenditures by the elderly who experienced illness. This result is robust to controlling for total household expenditures per capita, ruling out income effects as the main channel. Consistent with pensions increasing elderly bargaining power, we find that pensions significantly increase medical expenditures only for those elderly who co-reside with children or grandchildren but have no effect on those who live independently.
Keywords: J14; J26; 330; medical expenditures; pension; elderly; intra-household bargaining; regression discontinuity design; People's Republic of China